Seroprevalence and Associated Risk Factors of Hepatitis E Virus Infection Among Blood Donors in Tripoli, Libya - Albasheeri, Ali; Huwiage, Goma; Nami, Abdurrazag; Ellafi, Ahlam; Amara, Khadija; Mahmoud, Abdusalam (AlQalam Journal of Medical and Applied Sciences, 2024)
Hepatitis E (HE) is a transfusion-transmitted viral disease caused by the Hepatitis E virus (HEV). There are currently no national seroprevalence reports for Libyan blood donors. This study therefore aimed to evaluate HEV risk to blood safety by assessing the prevalence of anti-HEV IgG and anti-HEV IgM among Libyan healthy blood donors. A total of 267 serum samples were collected from blood donors. Using a questionnaire form, the risk factors for HEV infection of all blood donors were gathered. The sera of the blood donors were screened for anti-HEV IgM and anti-HEV IgG using ELISA kits (DIA. PRO Srl, Milan, Italy). The statistical significance of the association between dependent and independent variables was evaluated using the chi-square test. A P-value < 0.05 was considered an indicator of statistical significance. The overall seroprevalence of HEV infection was 5.24% (14/267). Of the 267 blood donors, 12 (4.49%) tested positive for anti-HEV IgG antibodies. In contrast, 2 (0.74%) tested positive for anti-HEV antibodies (IgM and IgG). Our seroprevalence of anti-HEV IgG was significantly associated with increased age, marital status, the technique of washing hands before eating, and smoking habit, and it was significantly low in blood donors who eat in cafes and restaurants. The overall seroprevalence of HEV infection was low in Libya. HEV is not currently prevalent among blood donors in Tripoli, Libya and poses little threat to the national blood supply. Therefore, current blood donor screening protocols are sufficient. الالتهاب الكبدي هـ هو مرض فيروسي ناشئ ينتقل عن طريق الدم و يسببه فيروس التهاب الكبد هـ. لا توجد حاليًا تقارير وطنية عن الانتشار المصلي لعدوى فيروس الالتهاب الكبدي هـ، للمتبرعين بالدم الليبيين. لذلك هدفت هذه الدراسة إلى تقييم خطر فيروس الالتهاب الكبدي هـ، على سلامة نقل الدم بطرابلس، ليبيا، من خلال تقييم انتشار الأجسام المضادة لفيروس الالتهاب الكبدي هـ (الغلوبولين المناعي ج والغلوبولين المناعي م)، بين المتبرعين بالدم في طرابلس، ليبيا. تم جمع 267 عينة مصل من المتبرعين بالدم. تم جمع العوامل الاجتماعية والديموغرافية، وعوامل الخطر المرتبطة بفيروس التهاب الكبد هـ، لجميع المتبرعين بالدم باستخدام نموذج إستبيان،و بإستخدام تقنية الإليزا، تم فحص عينات المتبرعين بالدم، للكشف عن وجود الأجسام المضادة لفيروس الالتهاب الكبدي هـ (الغلوبولين المناعي ج والغلوبولين المناعي م). الأهمية الاحصائية للارتباط بين المتغيرات التابعة والمستقلة، تم تقييمها باستخدام اختبار مربع كاي. القيمة الاحتمالية أقل من 0.05، أعتبرت مؤشرا للأهمية الإحصائية. بلغ معدل الانتشار المصلي الإجمالي لعدوى فيروس التهاب الكبد هـ 5.24% (14/267). من بين 267 متبرعًا بالدم، كان اختبارالغلوبولين المناعي ج ايجابي لعدد 12 (4.49%) متبرعا بالدم. لم تكن نتيجة اختبار أي من المشاركين إيجابية بالنسبة لإختبار الغلوبولين المناعي م. في المقابل، كانت نتيجة إختبارالأجسام المضادة لفيروس التهاب الكبد هـ (الغلوبولين المناعي ج والغلوبولين المناعي م) لعدد 2 (0.74%) من المتبرعين بالدم إيجابية. ارتبط الانتشار المصلي للأجسام المضادة لفيروس التهاب الكبد هـ (الغلوبولين المناعي ج) ارتباط مهم إحصائيا مع زيادة العمر والحالة الاجتماعية وتقنية غسل اليدين قبل الأكل وعادة التدخين، وكان منخفضًا بشكل مهم إحصائيا في المتبرعين بالدم الذين يتناولون الطعام في المقاهي والمطاعم. كشفت الدراسة الحالية، ان معدل الانتشار المصلي الإجمالي لعدوى فيروس التهاب الكبد هـ منخفضا في ليبيا. عدوى فيروس الاتهاب الكبدي هـ، ليست منتشرة في المتبرعيين بالدم في طرابلس، ليبيا، وتشكل خطرا بسيطا على نقل الدم بداخل الوطن. وبالتالي فان بروتوكولات فحص المترعين بالدم الحالية، تعتبر كافية